Recital for Vibraharp - DAVIS, Thomas L. (C.L. Barnhouse Co, 1975)
1. Sarabande2. Prelude in C Major3. Nocturne4. Serenade5. Le Petit Berger6. La Fille aux Cheveux de Lin7. Brigg Fair8. Valse Trisque'9. A Theme for Goodbye10. Lament11. Toccata Avant12. The Ash Grove